Chemical composition of dried pulp of Arabica, Robusta and Liberica coffee varieties - Beloro, Lorenzo O.; Cornago,Djanna F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
In this study, proximate composition (including moisture, crude fat, crude protein, crude fiber, ash, and total available carbohydrate contents) and caffeine content of dried coffee pulp samples from three locally grown coffee varieties (Arabica, Robusta and Liberica) were investigated. Nitrogen-free extract was determined as percent difference based on the results of proximate analysis. UV/vis spectrophotometry method was used for caffeine determination with dichloromethane as extracting solvent. Proximate composition was observed to be significantly different (p<0.05) among dried coffee pulp samples, except for moisture and crude fiber contents. Moreover, the present study revealed that caffeine content of Arabica and Liberica were not significantly different (p>0.05) from each other; however, both values were significantly different (p<0.05) to that of Robusta. Robusta sample had the highest level of moisture, crude fat and crude fiber. Crude protein and ash were observed to be highest in Arabica sample while highest levels of TAC and NFE were observed in Liberica. Differences in chemical composition across varieties may be attributed to variation in genetic make-up and environmental conditions during cultivation.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Coffee -- Philippines -- Varieties; Coffee pulp -- Composition